Perancangan Ulang Komponen Condensate Booster Pump pada System Re-Injeksi di PLTP X - Adityawarman, Dzaky Fauzan Hilmy; Melkias, Alvera Apridalianti; Prayogo, Sapto (SURYA TEKNIKA, 2024)
PLTP X is a power plant located in West Java, at this time PLTP X uses 2 condensate booster pumps that experience a discrepancy between the pump operation area specification and the actual condition. This problem causes vibration and decreased efficiency thus causing damage to the pump components. The purpose of this research itself is to design pump components in the form of impellers, shafts, pegs, & volutes. Another goal is to calculate the energy savings resulting from the design. This research has a quantitative and experimental nature. The data used is operational data of the PLTP X and other secondary data issued by the PLTP X. The required technical specifications are a head ±130 m, a capacity of 60 m3/h, a rotation of 2970 RPM & an efficiency > 60%. Based on the results of this study, it was obtained that the pump is a type of low discharge high pressure centrifuge, then the design of this pump has a head of 128.4 m, a capacity of 60 m3/h, an efficiency of 67% and has succeeded in saving energy of 107586.16 kWh per year at its point of operation.